Influence of Intellectual Capital, Governance and CSR Disclosure on Real Estate Companies Share Returns Listed on Bei - Ristanti, Annisa Dyah; Dian Indira Kusuma, Poppy; Rafinda, Ascaryan (Ratio : Reviu Akuntansi Kontemporer Indonesia, 2024)
This research analyzes the influence of intellectual capital, good corporate governance, and corporate social responsibility disclosure on stock returns in property and real estate companies listed on the Indonesia Stock Exchange for 2018-2021. The population in this research are companies in the property and real estate sector listed on the IDX for the 2018-2021 period. The sample selection in this study used a purposive sampling method, and 34 companies could be used as samples over a four-year research period. The research results using multiple linear regression analysis processed with SPSS software show that (1) intellectual capital does not affect increasing stock returns. (2) good corporate governance affects increasing stock returns. (3) corporate social responsibility disclosure does not affect increasing stock returns.